Micro‐CT evaluation of sonically and ultrasonically activated irrigation on the removal of hard‐tissue debris from isthmus‐containing mesial root canal systems of mandibular molars. (4th March 2019) - Rödig, T.; Koberg, C.; Baxter, S.; Konietschke, F.; Wiegand, A.; Rizk, M.
Abstract: Aim: To evaluate the efficacy of sonically and ultrasonically activated irrigation on removal of accumulated hard‐tissue debris (AHTD) in mesial root canal systems of mandibular molars using micro‐computed tomographic (micro‐CT) analysis. Methodology: Forty mesial roots of mandibular molars with two independent canals joined apically by an isthmus (Vertucci type II) were selected. The root canals were instrumented using Reciproc R25 instruments, and specimens were scanned at a resolution of 10.5 μm. Subsequently, n = 10 roots were assigned to each of the four final irrigation groups such that the group means and variances were almost identical: sonically activated irrigation with EndoActivator (EA) or EDDY (ED), ultrasonically activated irrigation (UAI) and manual irrigation without activation (MI). The final irrigation procedures were performed using a total of 5 mL 1% NaOCl and 5 mL 15% EDTA per canal over 5 min with activation time of 4 × 20 s. Reconstructed data sets were coregistered, and the mean percentage reduction of AHTD after final irrigation was compared statistically between groups using analysis of variance at a significance level set at 5%. Results: A significant reduction of AHTD was achieved after final irrigation in all groups ( P < 0.05), ranging from 44.1% to 66.8%. The vol% of debris after irrigation was 3.7 ± 1.9% for EA, 3.3 ± 2.3% for ED, 2.1 ± 1.6% for UAI and 4.4 ± 2.3% for MI, with no significant difference between groups ( P > 0.05). Conclusions: None of the final irrigation protocols completely removed AHTD from mesial root canal systems in extracted human mandibular molars. Sonically and ultrasonically activated irrigation performed no better compared to manual irrigation.